Integrating Leadership Styles with High-Performance Work Systems: Pathways to Organizational Excellence - Muhammad Khan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The research article explores the nuanced relationship between leadership styles and the effectiveness of High-Performance Work Systems (HPWS) within organizations. HPWS are strategic approaches that integrate various human resource practices—such as selective hiring, comprehensive training, employee involvement, and incentive compensation—to enhance organizational performance. Leadership plays a pivotal role in the successful implementation of HPWS, influencing organizational culture, employee engagement, and the overall effectiveness of these systems. This study delves into how different leadership styles, including transformational, transactional, and servant leadership, influences the deployment and sustainability of HPWS. Through theoretical analysis and examination of empirical studies, the research identifies key challenges in aligning leadership with HPWS, such as resistance to change and cultural misalignments, and proposes strategies to overcome these obstacles. Additionally, real-world case studies illustrate the practical implications of leadership on HPWS outcomes, providing insights into how organizations can harness leadership to enhance the success of HPWS. The findings highlight the importance of strategic leadership development and the need for leaders to embody the values and behaviors that HPWS promote. This study contributes to the understanding of the critical interplay between leadership and HPWS, offering valuable perspectives for researchers, practitioners, and organizational leaders aiming to leverage HPWS for improved performance and competitive advantage.